Plasma Instability Evolution and Particle Heating in the Foot Region of Perpendicular Shocks in Young Supernova Remnants - K. F. F. Law; S. Fujioka; Y. Ohira (The Astrophysical Journal)
Particle acceleration from collisionless shocks is a key mechanism in the generation of cosmic rays. In particular, shocks in young supernova remnants (SNRs) are considered to be a major source of galactic cosmic rays. This study investigates the early-stage plasma instability evolution and subsequent electron and ion heating in the foot region of high-Mach-number perpendicular shocks in young SNRs, using 2D particle-in-cell simulations. Unlike previous simulations that cover larger regions of the shock structure—including the downstream, shock, and upstream regions—our simulations are local, limited to the shock transition region, and focus on practical parameters with a nonrelativistic shock velocity ( v  ≈ 0.02 c ) and the standard mass ratio between protons and electrons. We examined scenarios with and without the presence of return protons, and our results reveal that the Buneman instability, followed by the ion two-stream instability, dominates the early electron-heating process. We observed long-lasting ion heating in the case without return protons and note that the Weibel instability did not emerge within the simulation time frame. These findings enhance the understanding of plasma behavior in young SNR shocks and suggest that local simulations with practical parameters are crucial for exploring electron-heating mechanisms, while also highlighting the conditions under which the Weibel instability may or may not emerge.